PENERAPAN METODE CREDITRISK+ DALAM PENGUKURAN RISIKO KREDIT KENDARAAN BERMOTOR (KASUS PADA PT X) - Meilani, Any (Jurnal Organisasi dan Manajemen, 2010)
Identify and measure credit risk by using a method in accordance with the characteristics of finance companies is one of a prudent first step in minimizing potential losses. Potential losses can be seen from the Non Performing Loan (NPL) and recovery rate of the company. Credit risk measurement remains important as preventive and anticipatory measures for a finance company in managing the potential consumer default in fulfilling their obligations. By using 36 months of credit risk in motor vehicles (2006-2008) which includes the number of units of motor vehicles, the amount of exposure, collectability and recovery rate can be calculated expected Loss, unexpected loss and economic capital. Results showed that both the expected Loss and unexpected loss from year to year increase. Also with the economic capital increases annually. However, if the economic value associated with authorized capital owned by PT "X" each year, it can be concluded that the capital is still sufficient to cover possible losses caused by credit default unexpected losses. Testing the model using back testing and Likelihood Ratio, indicates that during the observation period the number of adverse events "X" with the level of losses that exceed the value of the vehicle financing credit VaR is still below the threshold amount of loss that can be tolerated. In other words the risk measurement method using a motor vehicle financing CreditRisk+ is acceptable and accurate enough to measure the risk of motor vehicle financing PT "X".